(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
The Impact of Tourism Attributes and Services on Revisit Intention to Subak Jatiluwih Agrotourism, Tabanan. Agrotourism is a form of tourism that integrates the agricultural sector with the tourism industry, where agricultural areas not only function as production land, but also offer tourist attractions in the form of natural beauty and cultural values. One destination that develops this potential is Jatiluwih Subak Agrotourism, which is known as a world cultural heritage. This study aims to determine the effect of destination attributes and service quality on tourist return visit intention. The research was conducted with a quantitative approach using the SmartPLS-based Structural Equation Modeling (SEM) method. Data were collected through questionnaires of tourists visiting Subak Jatiluwih, using stratified sampling technique. The results showed that attributes and service quality had a significant effect on return visit intention. The findings provide important implications for managers to focus more on improving the quality of tourist information, accessibility, and the provision of cultural and nature-based tourism activities to encourage loyalty and sustainability of tourism in the area.